Pre transplant herbicide application and cultivation to manage weeds in southeastern broccoli production. (October 2019) - Cutulle, Matthew; Campbell, Harrison; Couillard, David M.; Ward, Brian; Farnham, Mark W.
Abstract: The East Coast broccoli ( Brassica oleracea, L group Italica) industry in the United States is growing, and optimizing weed control strategies in southeastern US environments is important for the expansion of commercial broccoli in the region. Research was conducted in Charleston, SC to evaluate the impact of four herbicides (pyroxasulfone, napropamide, S -metolachlor, and oxyfluorfen) applied pre-transplant and two cultivation practices (cultivation after transplanting or no cultivation) on weed control, broccoli safety, broccoli quality characteristics and yield attributes for two broccoli hybrid cultivars, Emerald Crown and Lieutenant. The trials were conducted during the fall of 2017 and the spring of 2018. No injury was observed during the fall trial, though injury occurred from napropamide and pyroxysulfone application in the spring. Generally, weed competition did not significantly influence quality ratings at all. Stem diameter of broccoli was generally greater with cultivation, though likely due to enhanced aeration of broccoli roots than the added weed control. Based on the results of these studies cultivation is important for maximizing broccoli yield characteristics in coastal South Carolina while herbicide application may be less critical. Highlights: Herbicides were not necessary to maximize broccoli quality and yield. Cultivation had a significant effect on several yield and quality parameters. Residual herbicides are more injurious during the spring growing season in the Eastern US.